Oral antidiabetic treatment in type-2 diabetes in the elderly: balancing the need for glucose control and the risk of hypoglycemia - Bramlage, Peter; Gitt, Anselm Kai (Cardiovascular diabetology, 2012)
We aimed at identifying variables predicting hypoglycemia in elderly type 2 diabetic patients and the relation to HbA1c values achieved.